A two-layer dynamic voltage regulation strategy for DC distribution networks with distributed energy storages. (September 2020) - He, Li; Li, Yong; Shao, Xia; Cao, Yijia; Luo, Longfu; Liu, Ling; Shahidehpour, Mohammad
Highlights: A two-layer voltage regulation strategy is proposed for dc distribution network. The SoC constraint is designed in the primary control for maintaining SoC. The economic factors are considered for DESs' economic operation. Abstract: In this article, a two-layer bus voltage regulation strategy with distributed energy storages (DESs), is proposed for dc distribution networks. The developed droop principle based on the power coupling characteristics of ac/dc interface is derived as the basis of the primary control. Besides, the state of charge (SoC) of DES unit is considered inherently in the primary regulation, which can effectively contribute to the long-term performance and life span of DES unit. Then, the cost characteristics of DES device and its connecting converter are analyzed in detail, and the secondary voltage regulation is accordingly designed based on the developed dynamic equal incremental cost principle. The proposed two-layer voltage regulation can achieve the economic power dispatch during the multi-bus voltage regulation without deteriorating the voltage quality, which can obtain a trade-off between the voltage performance improvement and the DESs economic operating. The performance of the proposed control strategy is validated with different operating conditions in the case studies.